Influence of the rate of ethanol production and accumulation on the viability of Saccharomyces cerevisiae in "rapid fermentation". - Nagodawithana, T W (1976)
Whereas "rapid fermentation" of diluted clover honey (25 degrees Brix) fortified with yeast nutrients using 8 X 10(8) brewers' yeast cells per ml resulted in an ethanol content of 9.5% (wt/vol; 12% vol/vol) in 3 h at 30 C, death rate of the yeast cells during this period was essentially logarithmic. Whereas 6 h was required to reach the same ethanol content at 15 C, the yeast cells retained their viability. Using a lower cell population (6 X 10(7) cells/ml), a level at which the fermentation was no longer "rapid," the yeast cells also retained their viability at 30 C. Ethanol added to the medium was much less lethal than the same or less quantities of ethanol produced by the cell in "rapid fermentation." It was considered possible that ethanol was produced so rapidly at 30 C that it could not diffuse out of the cell as rapidly as it was formed. The hypothesis was postulated that ethanol accumulating in the cell was contributing to the high death rate at 30 C. It was found that the intracellular ethanol concentration reached a level of approximately 2 X 10(11) ethanol molecules/cell in the first 30 min of fermentation at 30 C. At 15 C, with the same cell count, intracellular ethanol concentration reached a level of approximately 4 X 10(10) ethanol molecules/cell and viability remained high. Also, at 30 C with a lower cell population (6 X 10(7) cells/ml), under which conditions fermentation was no longer "rapid," intracellular ethanol concentration reached a similar level (4 X 10(10) molecules ethanol/cell) and the cells retained their viability. Alcohol dehydrogenase (ADH) lost its activity in brewers' yeast under conditions of "rapid fermentation" at 30 C but retained its activity in cells under similar conditions at 15 C. ADH activity was also retained in fermentations at 30 C with cell populations of 6 X 10(7)/ml. It would appear that an intracellular level of about 5 X 10(10) ethanol molecules/cell is normal and that this level does not damage either cell viability or ADH activity. Higher intracellular ethanol concentrations, such as 2 X 10(11) molecules ethanol/cell (a fourfold increase in intracellular ethanol concentration), are accompanied by inactivation of ADH and loss of cell viability.